Gender and sex differences in adherence to a Mediterranean diet and associated factors during the COVID-19 pandemic: a systematic review - Brandt, Gerrit; Pahlenkemper, Marie; Ballero Reque, Cristina; Sabel, Luisa; Zaiser, Christopher; Laskowski, Nora M.; Paslakis, Georgios (Frontiers in Nutrition, 2025)
BackgroundThe COVID-19 pandemic has led to significant lifestyle changes, including alterations in dietary habits and increases in sedentary behavior. The Mediterranean diet (MD) has been associated with various health benefits, which are especially important given the health challenges posed by the pandemic. During the pandemic, an overall shift towards consuming more highly processed foods has been observed.MethodsThis systematic review investigated adherence to MD during the COVID-19 pandemic, focusing on gender differences and factors influencing adherence to MD in the general public. The literature search focused on papers published between January 1, 2019, and July 8, 2024, across various databases such as Web of Science (WOS), Scopus, PubMed MEDLINE, and PsycINFO.ResultsFollowing the PRISMA guidelines, this search identified 14,347 references, of which 5,734 were duplicates. After a thorough multi-level screening process, 29 studies, encompassing 55,242 participants, met the inclusion criteria. While seven studies reported that men adhered to a MD more than women during the COVID-19 pandemic, 12 studies also indicated that women had higher adherence to a MD compared to men. Nine studies, however, found no significant gender differences in MD adherence. Additionally, older age, higher education levels, higher socioeconomic status, and increased physical activity were linked to greater adherence to a MD in the pandemic context.ConclusionGender-specific differences in dietary behavior are influenced by factors such as socioeconomic status, gender roles, and pandemic phases as well as biases in sample composition and methodological weaknesses. Significant gaps in the evidence, particularly concerning sexual and gender minorities, are highlighted.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=421727.